Evaluasi Pembelajaran Ekonomi dalam Mendukung Pengalaman Belajar Mendalam - Sabon, Yuliana Olga Siba; Palimbu, Lamba Toding; Edwar, Rizka Cintya (Indo-MathEdu Intellectuals Journal, 2025)
Economic learning plays an important role in developing students’ critical thinking skills and rational decision-making abilities. However, the practice of economic learning in schools still faces various challenges, which necessitate a comprehensive evaluation. This study aims to evaluate the implementation of economic learning within the context of students’ deep learning experiences. This study employed an evaluative research approach by applying three levels of the Kirkpatrick evaluation model, namely reaction, learning, and behaviour. Data were collected through questionnaires, interviews, and classroom observations conducted during the learning process. Data analysis was carried out using both qualitative and quantitative methods, while data validity was ensured through triangulation of data collection techniques. The results indicate that across all aspects of deep learning experiences, including joyful learning, mindful learning, and meaningful learning, students’ responses fall within the good to very good categories. Furthermore, the evaluation results reveal positive changes in students’ learning behaviours, particularly in terms of increased responsibility, initiative, and learning autonomy in economic learning. These findings suggest that evaluating economic learning based on deep learning experiences can serve as a reflective foundation for improving the quality of classroom instruction.